Population structure and reproductive dynamics of the ridged swimming crab Charybdis natator in the southern Taiwan Strait of China: significant changes within 25 years - Lin, Bai-an; Jiang, Yan; Liu, Min (Frontiers in Marine Science, 2023)
The ridged swimming crab Charybdis natator (Portunidae) is a commercially important crustacean species in China. The purpose of this study is to compare its population structure and reproductive pattern within the same fishing area (the southern Taiwan Strait) from two datasets over 25 years; one from 1994−1996 (the early years of the C. natator fishery) and the other from 2019. The overall sex ratio (male:female) changed from a male bias (1:0.76, p < 0.01) in 1994−1996 to a female bias (1:1.38, p < 0.01) in 2019. Male body sizes (carapace width, CW) were significantly larger than those of females in both datasets (p < 0.05). The average CW and body weight (BW) of males and females in 2019 were significantly smaller (p < 0.01) and lighter (p < 0.01) than those in 1994−1996. The maximum body size and the proportion of large-sized individuals (CW > 10 cm) decreased dramatically over 25 years. One spawning peak season was identified from each dataset, i.e., March−August 1994−1996 and February−April 2019, revealing a 1-month shift. The minimum body sizes for female maturation (carrying eggs) were 6.9 cm CW in 1994−1996 and 6.1 cm CW in 2019, an 11.6% reduction over 25 years. For the first time, the CW at 50% female maturation, the relationship between female absolute fecundity and CW, and egg diameters were obtained from the 2019 dataset, which can be applied in the future comparisons. Recent studies have revealed a consistent spawning peak in February–April for several commercially important crabs in the southern Taiwan Strait. These findings should be considered in crab fishery management. Furthermore, both fishery- and environment-associated factors influencing crustacean population structure and reproductive dynamics merit further investigation.